2008
DOI: 10.1248/cpb.56.878
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Surface States of Colloidal Probucol Nanoparticles Evaluated by Atomic Force Microscopy

Abstract: Morphology and surface states of colloidal probucol nanoparticles after dispersion of probucol/polyvinylpyrrolidone (PVP)/sodium dodecyl sulphate (SDS) ternary ground mixture into water were investigated by atomic force microscopy (AFM). The observed particles had core-shell structure, i.e. drug nanocrystals were covered with PVP and SDS complex. The AFM phase image and the force curve analyses indicated that probucol nanoparticles with PVP K17 showed layer structure, compared to those with PVPK12. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The structural difference was accountable in terms of the molecular states of PVP-SDS complex on the particle surface. These findings support not only the mechanism of drug nanoparticle formation but also the in vivo absorption results with the almost same particle size of 40 nm [ 36 ].…”
Section: Characterization Of Nanocrystalssupporting
confidence: 79%
“…The structural difference was accountable in terms of the molecular states of PVP-SDS complex on the particle surface. These findings support not only the mechanism of drug nanoparticle formation but also the in vivo absorption results with the almost same particle size of 40 nm [ 36 ].…”
Section: Characterization Of Nanocrystalssupporting
confidence: 79%
“…The two-slope behavior possibly represents a signature of core-shell structures. 42 For the NC particles the first slope value was 0.43 and the second slope value was 0.67 while for the LNC particles these values were 0.65 and 0.81, respectively. It can be noted that the difference between the slopes was close to 40% for NCs and 20% for LNCs in comparison with the substrate.…”
Section: Study Of the System Deformation Propertiesmentioning
confidence: 89%
“…It was found that the high redispersiblility of Sus-SD products was reproducible among batches even if the conditions of spray-drying process were changed. It was also reported that the ternary ground mixture of drug/PVP/SLS could produce the colloidal drug nanoparticles when dispersing in water (34,35). From the human health point of view, it would be greatly advantageous that the nano-dispersion was achieved with much higher drug content (drug:PVP:SLS=40:5:1) in this study compared to the previous one (drug:PVP:SLS=1:3:1).…”
Section: Pharmaceutical Performance Of Dry Nanosuspensionmentioning
confidence: 61%